ELABORACIÒN DE UN PLAN DE COMUNICACIÒN PARA EL SEGURO SOCIAL CAMPESINO DEL CANTÓN QUEVEDO - Osorio Pluas, Edgar Andres (2022)
Communication is a fundamental part of business success, the way of interacting in a spoken or written way, favoring each of the steps that are carried out within the organizational area of institutions, whether public or private. The objective of this research is to develop an internal communication plan to improve communication development in the Peasant Social Security of the Quevedo canton. The project seeks to benefit those who work in the institution, so that each of the processes that are developed are elaborated. efficiently, working as a team, generating ideas and motivating them to be effective in each role they perform. To obtain information on the subject, it was necessary to apply the investigative techniques and methods through a survey, determining if the communication that is handled affects the external area where sufficient information is not provided to those who are associated, which affects many of them. unaware of their responsibilities and benefits they have.